Risk Factors for Underweight in Toddler Age 12-59 Months - Sucia, Annisa; Kosnayani, Ai Sri; Husnul, Nisatami (LPPM STIKes Muhammadiyah Ciamis, 2025)
Introduction: Underweight toddlers are conditions where a toddler's weight does not correspond to his or her proper age, which can then affect the growth and development of toddlers. Objective: This study aims to determine the risk factors for underweight in toddlers aged 12-59 months in Cikunten Village, Singaparna District, Tasikmalaya Regency.. Method: The research method used was an observational study with a case control design. The total sample was 82 toddlers (41 cases, 41 controls). The control sampling technique uses a 1:1 matching technique with simple random sampling. The instruments in this study used a characteristics questionnaire, Clean and Healthy Living Behavior (PHBS) household questionnaire, SQ-FFQ form and food photo books for nutritional adequacy levels. Result: The results of analysis using chi-square and OR show that the risk factors for underweight in toddlers aged 12-59 months in Cikunten Village, Singaparna District, Tasikmalaya Regency were family income (p-value 0.001; OR 5.56), history of infectious diseases (p-value 0.033; OR 3.23), energy adequacy level (p-value 0.000; OR 6.59), carbohydrates (p-value 0.000; OR 5.84), protein (p-value 0.003; OR 4.54), and fat (p -value 0.000; OR 5.87), as well as household PHBS (p-value 0.002; OR 5.1). Conclusion: Low family income is at risk 5.56 times, history of infectious diseases 3.23 times, low energy adequacy level 6.59 times, carbohydrates 5.84 times, fat 6.87 times, protein 4.54 times, and household PHBS 5.1 times regarding the incidence of underweight in toddlers aged 12-59 months in Cikunten Village, Singaparna District, Tasikmalaya Regency.